Fibrina rica en plaquetas en la cicatrización de los tejidos periodontales - López-Pagán, Eduardo (2020)
Platelet-rich fibrin (FRP) is a fibrin membrane or clot that contains leukocytes, platelets, cytokines and growth factors; it is considered a biomaterial and second generation platelet concentrate that is obtained by centrifuging the patient's own blood. This review aims to evaluate the healing of periodontal tissues with the application of FRP. The review concludes that FRP is a good alternative to promote better healing, in addition to promoting other biomaterials in order to condition a better regeneration and a shorter period of time.